Primary cilia: a link between hormone signalling and endocrine-related cancers?. (19th October 2016) - O'Toole, Samuel M.; Chapple, J. Paul
Abstract : Primary cilia are sensory organelles that play a role as signalling hubs. Disruption of primary cilia structure and function is increasingly recognised in a range of cancers, with a growing body of evidence suggesting that ciliary disruption contributes to tumourigenesis. This review considers the role of primary cilia in the pathogenesis of endocrine-related cancers.